2010
DOI: 10.1053/j.ajkd.2010.05.024
|View full text |Cite
|
Sign up to set email alerts
|

A Computerized Provider Order Entry Intervention for Medication Safety During Acute Kidney Injury: A Quality Improvement Report

Abstract: Background Frequently, prescribers fail to account for changing kidney function when prescribing medications. We evaluated the use of a computerized provider order entry intervention to improve medication management during acute kidney injury (AKI). Study Design Quality improvement report with time series analyses. Setting & Participants 1598 adult inpatients with a minimum 0.5 mg/dl increase in serum creatinine over 48 hours following an order for at least one of 122 nephrotoxic or renally cleared medicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(103 citation statements)
references
References 45 publications
2
96
0
5
Order By: Relevance
“…The value of electronic alerts was shown in patients taking nephrotoxic drugs, in whom an email alert resulted in a 55% risk reduction of AKI (this study predated the current AKIN definition) (22). In a similar, more recent study, interruptive electronic alerts were also shown to improve medicines management in those with AKI (23). However, the alert system prompted responses in only 52% of cases and passive alerts were less effective.…”
Section: Discussionmentioning
confidence: 80%
“…The value of electronic alerts was shown in patients taking nephrotoxic drugs, in whom an email alert resulted in a 55% risk reduction of AKI (this study predated the current AKIN definition) (22). In a similar, more recent study, interruptive electronic alerts were also shown to improve medicines management in those with AKI (23). However, the alert system prompted responses in only 52% of cases and passive alerts were less effective.…”
Section: Discussionmentioning
confidence: 80%
“…Our study highlights the challenges of caring for patients with AKI and was conducted in a medical center with many medication safety strategies, including electronic medical records, CPOE with clinical decision support (17), and rounding clinical pharmacists. We could not quantify the impact of these safeguards on our outcome rates, but previous studies suggest substantial improvement (4,(46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%
“…Study data were collected as part of a quality improvement program with Institutional Review Board approval to improve drug safety (16). Briefly, the program featured CPOEbased clinical decision support (17,18), prospective monitoring, and as necessary, intervention by a clinical pharmacist through an electronic surveillance tool. Data for this observational study were collected at discharge by an independent outcome assessor.…”
Section: Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies looking at the efficacy of the systems currently in use have shown a 55% reduction in the risk of AKI in patients taking nephrotoxic drugs and an improvement in medicines management in 52%. 20,21 More recently, Selby et al described a real-time electronic resultsreporting system for AKI, which is linked to clinical guidelines on the hospital intranet. This system not only improved early recognition of AKI but also encouraged timely management of patients and early escalation of sick patients in accordance with local guidelines.…”
Section: Tip 5: Electronic Alertsmentioning
confidence: 99%